THE PARTICIPANTS AND THE RELATION OF ADHAN DISCOURSE AS REFLECTED ON THE MOSQUE STRUCTURE - Khristianto Khristianto (University of Muhammadiyah Purwokerto, 2010)
The design of a building surely considers the people who will use it. It may involve the number of people, their relationship, and how the people will use. As we see a building, we will get clues about the users or the people in the building. Reading a text can reveal who is the writer, to whom it is addressed, and the subject of person or parties it talks about, and the relationship among them. This gives an assumption that text and the architecture have participants to consider. The paper will try to explore relation mechanism among the participants of the adhan text, as a call for prayers for Moslem, as it is physically reflected on the mosque design. The participants in the discourse and the physical form are human and God. The operation of the relation there covers the horizontal relation among the individuals, and the transcendental relation between the individual of human as creature in one side and God as the creator, in another. These operations are explored through analysis on the semiotics of architectural elements: form, partition, size, and the arrangement of interior and exterior properties. Thus, mosque with its distinctive design is actually a piece of discourse which tells a story among of which there is a fact about the participants and their relation mechanism, just like a written commonly does.